Game poems : videogame design as lyric practice - Magnuson, Jordan (Amherst College Press, 2023)
"Scholars, critics, and creators describe certain videogames as being "poetic," yet what that means or why it matters is rarely discussed. In Game Poems: Videogame Design as Lyric Practice, independent game designer Jordan Magnuson explores the convergences between game making and lyric poetry and makes the surprising proposition that videogames can operate as a kind of poetry apart from any reliance on linguistic signs or symbols. This rigorous and accessible short book first examines characteristics of lyric poetry and explores how certain videogames can be appreciated more fully when read in light of the lyric tradition-that is, when read as "game poems." Magnuson then lays groundwork for those wishing to make game poems in practice, providing practical tips and pointers along with tools and resources. Rather than propose a monolithic framework or draw a sharp line between videogame poems and poets and their nonpoetic counterparts, Game Poems brings to light new insights for videogames and for poetry by promoting creative dialogue between disparate fields. The result is a lively account of poetic game-making praxis"--